Surgical Management of Atresia Ani in a Crossbred Calf - Pal, Madan; Ram, Kashi; Garhwal, Chander Pal; Virender (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Atresia ani is a congenital defect that describes the absence of a normal anal opening. It is fatal unless a surgical correction is carried out to provide an anal opening. In female, the rectum may break through the vagina, forming a rectovaginal fistula permitting defecation via the vulva. Surgical treatment of atresia ani is indicated to save the animal’s life and to improve body weight gain. Intestinal atresia has been reported as a congenital defect in all species of domestic animals (Gass and Tibboel, 1980). Atresia ani may be caused by genetic disorders (chromosomes or transgenesis), environmental factors, or a combination of both (Cassini et al., 2005). Monsang et al. (2011) reported a case of double vulva with atresia ani in a crossbred calf. Atresia ani should be treated by a surgical operation to solve the problem, improve body weight gain, and reduce economic loss. The present report records a case of atresia ani in a crossbred cow-calf and its successful surgical correction.